Analysis of Kirana Bouquet's Competitive Advantage in Bandar Lampung Based on Resource-Based View (RBV) - Alyatur Rofiah; Silvita Sari; Vicky F. Sanjaya (Journal of Innovation, Business Management and Entrepreneurship, 2025)
This study aims to analyze the competitive advantage of Kirana Bouquet in Bandar Lampung based on the Resource-Based View (RBV) framework. RBV emphasizes that sustainable competitive advantage is formed through the utilization of internal resources that are valuable, rare, inimitable, and non-substitutable. This research employs a descriptive qualitative method with a case study approach to obtain an in-depth understanding of the characteristics of the business’s resources and capabilities. Data were collected through in-depth interviews with the business owner and analyzed to identify the role of tangible resources, intangible resources, and operational capabilities in supporting competitiveness. The findings indicate that intangible resources are the most dominant factor in building the competitive advantage of Kirana Bouquet. Creativity in bouquet design and wrapping, high-quality service, business reputation built through customer reviews, and pricing decisions aligned with market conditions are key elements that differentiate the business from its competitors. In addition, the use of digital technologies such as social media, online marketplaces, and cashless payment systems further strengthens the marketing strategy and operational efficiency. However, the less strategic location of the shop remains an obstacle to increasing exposure to potential new customers. Overall, this study emphasizes that the optimal management of internal resources is essential for creating and sustaining the competitive advantage of Kirana Bouquet.